PERUBAHAN KEARIFAN LOKAL MAPALUS TANI DI KELURAHAN RURUKAN SATU KECAMATAN TOMOHON TIMUR - Cheril Anita Rantung; Jane Sulinda Tambas; Benny Adrian Berthy Sagay (Sam Ratulangi University, 2020)
This study aims to determine changes in local wisdom of Mapalus Tani in Rurukan Satu Subdistrict, East Tomohon District. This research was conducted from February 2019 to April 2019. This research was obtained through in-depth interviews with several sources, informants / respondents using interview guides and being interviewed directly. The sampling method was carried out by snowball. The results showed that there had been changes in the values, norms and organizational structure of Mapalus Tani as stated by all the informants, informants / respondents interviewed while on the equipment some respondents said there had been no changes. Among other values, there are changes where there are no longer customs such as ma'tambor, pontuong, rituals before leaving for the garden, as well as changes in habits when going to the garden. In the norm, among others, there was a change where there was no longer a rule for labor to change energy but changing energy could be replaced by money. I doubt too is no longer as strict as it used to be. The organizational structure of Mapalus Tani changed, among others, the leader of the Mapalus Tani was no longer a tumutuuz who became the leader of the customs and rituals in Mapalus Tani. There was also a change in the equipment where the rope commonly used in Mapalus Tani, which is usually made of forest ropes that spread across the trees, was replaced with plastic ropes. Nevertheless Mapalus Tani still exists and exists and carries out Mapalus activities despite the various changes that have occurred. People who are members of Mapalus Tani are assisted in overcoming / reducing the burden of financing their land management.